Classic Signaling Pathways in Alveolar Injury and Repair Involved in Sepsis-Induced ALI/ARDS: New Research Progress and Prospect. (18th June 2022) - Li, Wenli; Li, Duo; Chen, Yuansen; Abudou, Halidan; Wang, Haiwang; Cai, Jinxia; Wang, Yiping; Liu, Ziquan; Liu, Yanqing; Fan, Haojun
Abstract : Sepsis is a common critical clinical disease with high mortality that can cause approximately 10 million deaths worldwide each year. Acute lung injury (ALI) or acute respiratory distress syndrome (ARDS) is a common clinical complication of sepsis, which occurs primarily as diffuse alveolar injury, hypoxemia, and respiratory distress. The mortality rate of ALI/ARDS is as high as 30%-40%, which greatly endangers human health. Due to the unclear pathogenesis of ALI/ARDS, its treatment is still a worldwide problem. At present, clinical treatment mainly relies on lung-protective ventilation, prone position ventilation, and fluid management. However, there is a lack of effective and specific treatment measures. In recent years, domestic and foreign scholars have committed to basic research on ALI/ARDS, trying to further clarify its pathogenesis and find new targets and methods for the treatment of ALI/ARDS. In this review, we summarize the signaling pathways related to alveolar injury and repair in sepsis-induced ALI/ARDS and their latest research progress. They include the NF- κ B, JAK2/STAT3, mitogen-activated protein kinase (MAPK), mTOR, and Notch signaling pathways. Understanding the molecular mechanisms of these signaling pathways in sepsis-induced ALI/ARDS may provide new targets and ideas for the clinical treatment of this disease.